WORK SYSTEM ANALYSIS OF POWER SUPPLY IN OPTIMIZING ELECTRICITY ON PERSONAL COMPUTER (PC) - Sudarmaji, Sudarmaji (TURBO [Tulisan Riset Berbasis Online], 2017)
Working Principles DC Power Supply - is an energy source for a computer to operate. The power supply changes the current from AC 110 volts to 60Hz or 220 volts 50Hz to DC + 3.3 volts, +5 volts and + 12 volts. Power Supply must carry a good and stable DC power supply so the system can run well. Tools running on the voltage supplied by the onboard voltage regulator, for example RIMM and RIMM require 2.5 volts while AGP AX and cards require 1.5 volts, both supplied by the onboard regulator of the motherboard. In addition to supplying power, the Power Supply can prevent the computer from starting until a Power Supply voltage exists at a predetermined area. Power Good is a sign of a special test that is sent to the motherboard as an active signal on the computer, usually marked by a green light when the power button is pressed. The current issued by the Power Supply is a direct current (DC), power output is composed of 200 watts, 250 watts, 300 watts, 350 watts, 400 watts to 600 watts. Computers with Intel Pentium 4 processors and above use power of 380 watts to 450 watts.Keywords: Power Supply, Computer, DC, Power Good, and volt